“As human beings, we cannot not learn”. An interview with Professor George Siemens on connectivism, MOOCs and learning analytics (Journal of Applied Learning and Teaching, 2020)
George Siemens is a globally-known higher-education expert who created the first Massive Open Online Course (MOOC) ever, together with Stephen Downes. He is Professor and Executive Director of the Learning Innovation and Networked Knowledge Research Lab at University of Texas, Arlington. In addition, he co-leads the development of the Centre for Change and Complexity in Learning (C3L) at University of South Australia. He has served as Principal Investigator on grants funded by the Bill & Melinda Gates Foundation and the Soros Foundation (to name but a few) and is the founding President of the Society for Learning Analytics Research.In this wide-ranging interview, George Siemens reconstructs his personal history as a lifelong learner and discusses his work, specifically on Connectivism, Massive Open Online Courses (MOOCs), and Learning Analytics. One of the leading thinkers in deepening our understanding on the impacts of technology on higher education and learning, George Siemens shares his personal experience of the utilitarian schooling system in his childhood which inspired him to have different perspectives on the interactions between education and technology, thus leading to his concept of Connectivism as well as his creation of MOOCs. He gives some insights on his seminal book, Knowing Knowledge, and elaborates on his perception of “knowledge” as well as the interactions of the four critical traits (diversity, autonomy, interactivity, and openness) in connective knowledge networks. Learning analytics is another focus for Siemens, and this relatively new, but quickly expanding, field can provide insights on the flow of information such as social activities, engagement patterns and a range of other factors that facilitate the quality of the learning experience for students. Siemens further emphasizes the cultural aspects of best practices of teaching and learning and also assessment in higher education. Siemens gives a preview of his future work which will focus on how human and artificial cognition may influence knowledge processes and their impacts on society